Reliability and Validity of Standing Lateral Radiograph Method for Measuring Acetabular Component Version: A Modified Cross‐table Lateral Radiograph Method. Issue 8 (16th June 2022) - Zhang, Wenhui; Xu, Jie; Li, Deng; Sun, Hao; Cai, Zhiqing; Chen, Meiyi; Ma, Ruofan
Abstract : Objectives: To investigate the effect of the X‐ray incidence angle on cup version measurements and the reliability and validity of standing lateral (SL) radiography for measuring cup versions. Methods: Cup versions under different X‐ray incidence angles were investigated by the 3D simulation analysis. Ninety‐three patients, who underwent primary total hip arthroplasty (THA) with postoperative SL radiographs and CT scans between April 2020 and December 2021, were retrospectively analyzed. SL radiography was taken under naturally standing position, correcting for the measurement error of pelvic tilt in cross‐table lateral (CL) radiography. Cup versions were measured on SL radiographs and CT images by two qualified orthopedic physicians. The intra‐ and inter‐observer reliabilities were assessed by intra‐class correlation coefficient. The consistency between radiographic and CT measurements was evaluated using Pearson correlation coefficient. Results: No significant differences in cup version measurements were observed between groups of different X‐ray incidence angles ( P = 0.663) in the 3D simulation analysis. All measurements had excellent intra‐ and inter‐observer reliabilities, with an intraclass correlation coefficient of >0.95. Mean cup version measurements from SL radiographs correlated well with those from CT scans ( r = 0.853, P < 0.001). The mean difference between radiographic and CT measurements was −0.49° (range −12.62° to 10.37°, SD 3.95°), and the majority of differences were within the 95% limits of agreement. Conclusion: The cup versions measured with SL radiography were close to the CT measurements. SL radiograph method is reliable and valid for measuring acetabular component version after THA. Abstract : Standing lateral radiography is an accurate and reliable method to assess the functional acetabular component version, enabling the evaluation of standing cup version and the identification of tilt direction of acetabular cup on single radiographic image.